2018
DOI: 10.1093/aob/mcx211
|View full text |Cite
|
Sign up to set email alerts
|

Feeling stretched or compressed? The multiple mechanosensitive responses of wood formation to bending

Abstract: This work leads us to propose new terminologies to distinguish the 'flexure wood' produced in response to multiple bidirectional bending treatments from wood produced under transient tensile strain (tensile flexure wood; TFW) or under transient compressive strain (compressive flexure wood; CFW). By highlighting similarities and differences between tension wood and TFW and by demonstrating that plants could have the ability to discriminate positive strains from negative strains, this work provides new insight i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 49 publications
0
45
0
Order By: Relevance
“…Although the treatment responses in terms of many of the macroscopic and biochemical traits tended to be similar between the two accessions, a notable exception were those involving the vascular system. Mechanical stimulation affects architectural and anatomical features in dicot stems (Paul‐Victor & Rowe, ; Rigo, ; Roignant et al, ), which may influence their mechanical properties (Shah, Reynolds, & Ramage, ). Mechanical stimulation has been reported to increase xylem tissue in a range of dicots (Hepworth & Vincent, ; Hunt & Jaffe, ; Jaffe, , ), but the situation in rice may be more complex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the treatment responses in terms of many of the macroscopic and biochemical traits tended to be similar between the two accessions, a notable exception were those involving the vascular system. Mechanical stimulation affects architectural and anatomical features in dicot stems (Paul‐Victor & Rowe, ; Rigo, ; Roignant et al, ), which may influence their mechanical properties (Shah, Reynolds, & Ramage, ). Mechanical stimulation has been reported to increase xylem tissue in a range of dicots (Hepworth & Vincent, ; Hunt & Jaffe, ; Jaffe, , ), but the situation in rice may be more complex.…”
Section: Discussionmentioning
confidence: 99%
“…Expression studies in Arabidopsis have shown that genes encoding cell wall‐associated proteins are enriched in response to mechanical stimulation (Lee et al, ), suggesting that changes in cell wall composition and architecture are involved in thigmomorphogenesis. A recent work reported that mechanical perturbations affect cell wall properties in trees (Roignant et al, ) and cell wall‐related traits play an important role in lodging resistance of rice (Fan et al, ; Li, Liu, Xu, & Xu, ; Ookawa et al, ) and wheat (Zheng et al, ). However, few studies have looked at cell wall‐related changes induced by more moderate wind and/or mechanical treatments (MTs).…”
Section: Introductionmentioning
confidence: 99%
“…The wood formed at the opposite side in each case is referred to as opposite wood (OW) and it is subjected to tensile and compressive forces in gymnosperms and angiosperms, respectively. In addition, wood formed in stems growing upright is subjected solely to vertical gravitational forces with respect to the long axis of xylogenic cells and it is often referred to as normal wood (NW), featuring intermediate MFA values when compared to RW and OW [7,40,41].…”
Section: Mfa As a Key Feature Of Scw Formationmentioning
confidence: 99%
“…Finally, wind-induced mechanical strains have been proved a major driver of wood growth rate 323 (Bonnesoeur et al 2016) and of wood anatomy (Roignant et al 2018). 324…”
Section: Discussion 251mentioning
confidence: 99%